PENGARUH GAYA HIDUP DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KOPI JANJI JIWA DI SUMMARECON KOTA BEKASI - Marsudi, Endra; Santoso, Teguh; Novalia Putri, Amanda (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to analyze the influence of lifestyle and word of mouth on the purchase decision of soul promise coffee. This research is a quantitative research. The sample in this study amounted to 130 respondents taken using purposive sampling techniques. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis used is multiple linear regression analysis, t test, F test, and determinant coefficient. The results in this study showed that based on the t test, the Word of Mouth variable was partially significant. Silmutantly, the Word of Mouth variable has a positive and significant effect on the decision to purchase soul promise coffee in Summarecon Bekasi city. While the Lifestyle variable partially has a significant effect, simultaneously the Lifestyle and Word of Mouth variables have a positive and significant effect on the decision to purchase soul promise coffee in Summarecon Bekasi city